2019
DOI: 10.1111/jcmm.14339
|View full text |Cite
|
Sign up to set email alerts
|

A‐kinase‐interacting protein 1 facilitates growth and metastasis of gastric cancer cells via Slug‐induced epithelial‐mesenchymal transition

Abstract: A‐kinase‐interacting protein 1 (AKIP1) has previously been reported to act as a potential oncogenic protein in various cancers. The clinical significance and biological role of AKIP1 in gastric cancer (GC) is, however, still elusive. Herein, this study aimed to investigate the functional and molecular mechanism by which AKIP1 influences GC. AKIP1 mRNA and protein expressions in GC tissues were examined by quantitative real‐time PCR (qRT‐PCR), Western blot and immunohistochemistry. Other methods including stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(59 citation statements)
references
References 19 publications
2
57
0
Order By: Relevance
“…[5][6][7] For example, clinical experiments in patients with gastric cancer illustrate that AKIP 1 high expression correlates with advanced TNM stage and lymph node metastasis, and mechanistic experiments exhibit that AKIP1 promotes gastric cancer cell proliferation, migration, and invasion by activating slug-induced EMT. 5 Another study displays that increased AKIP1 expression is associated with early recurrence and AKIP1 is a potential mediator of tumor metastasis via regulating Wnt/β-catenin signaling in hepatocellular carcinoma. 7 Furthermore, Wnt/β-catenin signaling, as an oncogenic signaling in both solid tumors and hematologic malignancies, is reported to be associated with the AML-related fusion proteins and FLT3-1TD mutation, which correlated with unfavorable survival profiles in AML patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7] For example, clinical experiments in patients with gastric cancer illustrate that AKIP 1 high expression correlates with advanced TNM stage and lymph node metastasis, and mechanistic experiments exhibit that AKIP1 promotes gastric cancer cell proliferation, migration, and invasion by activating slug-induced EMT. 5 Another study displays that increased AKIP1 expression is associated with early recurrence and AKIP1 is a potential mediator of tumor metastasis via regulating Wnt/β-catenin signaling in hepatocellular carcinoma. 7 Furthermore, Wnt/β-catenin signaling, as an oncogenic signaling in both solid tumors and hematologic malignancies, is reported to be associated with the AML-related fusion proteins and FLT3-1TD mutation, which correlated with unfavorable survival profiles in AML patients.…”
Section: Discussionmentioning
confidence: 99%
“…A‐kinase interacting protein 1 (AKIP1), a molecular regulator of protein kinase A, is reported to serve as an adaptor or structural intracellular protein and is localized to the cytoplasm, nucleus, and mitochondria . Recent studies reveal that AKIP1 contributes to the tumorigenesis angiogenesis, lymph angiogenesis, and invasiveness in several solid tumors, including breast cancer, colorectal cancer, and gastric cancer, and it predicts worse survival profiles in patients with cancer, suggesting that AKIP1 functions as an oncogene and may be an effective prognostic marker in these cancers . Whereas in hematologic malignancies, the role of AKIP1 is limitedly studied.…”
Section: Introductionmentioning
confidence: 99%
“…Another study discloses that AKIP1 downregulation inhibits cell motility and cell invasion through suppressing Akt/GSK‐3β/Snail pathway in breast cancer cells . These data indicate that AKIP1 might regulate some factors such as CXC chemokines and ZEB1 or mediate some processes such as Slug‐induced EMT and Akt/GSK‐3β/Snail pathway to promote cell proliferation and cell invasion, thereby facilitates tumorigenesis and invasiveness in some solid cancers …”
Section: Discussionmentioning
confidence: 93%
“…A‐kinase interacting protein 1 is initially reported as human breast cancer‐associated gene 3 (BCA3) whose biological role is largely unknown . Recently, some studies have identified AKIP1 as a gene overexpressed in multiple human cancer cells, and it might participate in the tumorigenesis and invasiveness . For example, an experiment shows that AKIP1 induces the autocrine effect of CXCL1, CXCL2, and CXCL8 to enhance cervical cancer cell proliferation in vitro and promote tumor growth in vivo .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation